Combined magnetic biochar and ryegrass enhanced the remediation effect of soils contaminated with multiple heavy metals - Xuening Li; Ruipu Li; Mengqi Zhan; Qian Hou; Haoyu Zhang; Guangqi Wu; Liqun Ding; Xiaofei Lv; Yan Xu (Environment International, 2024)
Biochar is a very promising material for soil remediation. However, most studies mainly focus on the adsorption ability of biochar on one heavy metal, which is difficult to evaluate the actual remediation effect since soils were contaminated with multiple heavy metals. In order to improve the soil remediation efficiency, we used the joint remediation method of magnetically modified biochar and ryegrass to remediate the soil polluted by compound heavy metals (chromium, nickel, copper, zinc, arsenic and cadmium), and evaluate the effect on the process of organic carbon mineralization in polluted soils. It was found that magnetic biochar and ryegrass together decreased the concentrations of Cr, Ni, Cu, Zn, As, and Cd in soils by 24.12 %, 23.30 %, 22.01 %, 9.98 %, 14.83 %, and 15.08 %, respectively, and reduced the available fractions. Ryegrass roots were the main accumulation part of heavy metals, and the order of enrichment effect was ranked as Zn > As > Cr > Cu > Ni > Cd. In addition, magnetic biochar can maintained the stability of the organic carbon pool, and inhibited the emission of volatile organic compounds from ryegrass. Overall, this study indicates that magnetic biochar spheres combined with ryegrass is an effective method for heavy metals co-contaminated soils, and has the excellent remediation ability for actual co-contaminated soils.